Ritual Kaghoghoniwi Terhadap Orang Yang Telah Meninggal Pada Masyarakat Muna Di Desa Bangkali - WaOde Natasya Pratiwi; La Niampe; Komang Wahyu Rustiani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The kaghoghoniwi ritual is a ritual performed by the Muna people in Bangkali Village during ceremonies of death and other celebrations. This ritual is not well known by the Bangkali village community, especially the milineal generation that can cause this ritual to become extinct, so researchers are interested in conducting research with the title